The intergroup dynamics of political cynicism: how perceived discrimination, outsiderness, and social capital relate to political cynicism among Moroccan and Turkish Belgians - Abts, Koen; Van Den Abbeele, Jef; Meeusen, Cecil; Meuleman, Bart (Frontiers in Sociology, 2024)
IntroductionThis study examines how intergroup dynamics shape political cynicism among Belgians of Turkish and Moroccan descent. Concretely, we examine whether perceptions of discrimination, feelings of ethnic outsiderness and social capital (in terms of associational membership) can explain minorities’ belief that political elites are selfish, incompetent, and immoral.MethodsWe analyse data from the Belgian Ethnic Minorities Election Study 2014.ResultsArguing that political cynicism includes blame attribution towards the political establishment, we distinguish between perceived group discrimination by the government, on the labor market, and in everyday life. As expected, political cynicism is closely related to perceptions of government discrimination, with no observed correlation with discrimination in the other domains. Next, we show that perceived ethnic outsiderness is also strongly related to increased feelings of political cynicism, further reinforcing the argument that cynics are concerned with their ethnic group’s excluded status and position in society. Finally, associational membership is only related to lower political cynicism when it is generated exclusively within ethnic boundaries; there was no relationship with cross-ethnic social capital.DiscussionOur findings show that intergroup indicators are highly relevant for understanding minorities’ political cynicism, but that the intergroup dynamics operate in complex and nuanced ways.